Evaluasi Kandungan Hasil Pengolahan Limbah Cair pada Point L PT. Petrokimia Gresik - Bagas Chrisma Pratama; Aussie Amalia (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
Fertilizers support the country's food security through State-Owned Enterprises (SOEs), including PT Petrokimia Gresik which is the most complete and largest fertilizer producer in Indonesia and produces several waste products, including industrial waste. The presence of liquid waste in the environment is undesirable because it has no economic value. Therefore, the need for waste disposal is very important. PT Petrokimia Gresik uses physical and chemical treatment. PT Petrokimia Gresik conducts liquid waste treatment through a series of processes consisting of two wastewater treatment units, balancer, line injection, and sludge treatment. The parameters analyzed are chemical oxygen demand (COD), total suspended solids (TSS), ammonia (NH3), total lizard nitrogen (TKN), fluoride, acidity (pH). After the study, the analysis results showed that the data of pollutant levels in wastewater were within the quality standards set by the regulations. However, the results of TKN (Kjeldahl total nitrogen), which is the amount of nitrogen bound to organic matter, were different.